Waste reduction of 3PL warehouse operation to overcome excessive overtime - Asmoro, Evelyn Nathaniela; Daryanto, Yosef (Jurnal Teknik Industri dan Manajemen Rekayasa, 2025)
Excessive overtime was a persistent issue in the warehouse operations of a 3PL company, where employees frequently exceeded the Indonesian government’s legal limit of 18 overtime hours per week due to daily working hours surpassing the 11-hour threshold. To analyse and address this problem, several structured methods were applied. Process Activity Mapping was used to classify activities into value-added, non-value-added, and necessary non-value-added categories, followed by Value Stream Mapping to visualize process flow and measure total cycle time. The 5 Whys analysis was then employed to identify root causes of delays and inefficiencies, leading to the application of the ECRS principle (Eliminate, Combine, Rearrange, Simplify) to redesign workflows and propose targeted improvements. As a result, the redesigned processes, supported by the modification of stock card formats, implementation of a kanban board, and development of Standard Operating Procedures, successfully reduced average working hours to 10.72 hours per day and decreased total process cycle time by 16.7 percent (65.9 minutes), demonstrating a notable improvement in warehouse efficiency and regulatory compliance.